2018
DOI: 10.1021/acs.jpclett.8b01697
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong Room-Temperature Phosphorescence from Supramolecular Behavior via Intermolecular Electronic Coupling in Pure Organic Crystals

Abstract: Ultralong room-temperature phosphorescence (RTP) of organic materials is extremely attractive for its tremendous potential use. However, the design of organic materials with ultralong and efficient RTP is very challenging due to the lack of general design principles. A new design principle for organic materials with ultralong room-temperature phosphorescence based on π-π-dominated supramolecular aggregates in crystal is proposed, and strong intermolecular electronic coupling with specific molecular alignment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 25 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…On the other hand, in the case of persistent RTP observed in aggregated state such as crystals, molecular design with charge transfer (CT) characteristics is expected as an important factor for inducing very rigid intermolecular interactions, and this design principle has been verified extensively . That said, some metal‐free aromatic molecules without CT characteristics still show persistent RTP in crystalline state . Particularly, the discussion of the origin of the suppressed k nr (RT) + k q (RT) in crystalline state has not progressed beyond the understanding that it may be induced by the rigidity of the crystalline state.…”
Section: Calculated Parameters Of Transfer Integral Reorganization Ementioning
confidence: 99%
“…On the other hand, in the case of persistent RTP observed in aggregated state such as crystals, molecular design with charge transfer (CT) characteristics is expected as an important factor for inducing very rigid intermolecular interactions, and this design principle has been verified extensively . That said, some metal‐free aromatic molecules without CT characteristics still show persistent RTP in crystalline state . Particularly, the discussion of the origin of the suppressed k nr (RT) + k q (RT) in crystalline state has not progressed beyond the understanding that it may be induced by the rigidity of the crystalline state.…”
Section: Calculated Parameters Of Transfer Integral Reorganization Ementioning
confidence: 99%
“…This causes the energy of the triplet state to return to the ground state in a non-radiative manner. [45][46][47][48][49]…”
Section: Long Lifetime Phosphorescence Propertymentioning
confidence: 99%
“…Two critical strategies, the inhibition of energy dissipation caused by non-radiative transitions and the promotion of intersystem crossing (ISC), have been proposed to develop efficient pure organic RTP materials. The method often adopted to suppress non-radiative transitions is to embed the phosphorescent chromophores into rigid matrixes, such as crystalline or amorphous hosts at an appropriate concentration. In the rigid matrix, non-radiative transition channels induced by molecular vibration can be efficiently suppressed and radiative transition turns into the dominant process. It is demonstrated that the enhanced n → π* transition can promote the ISC process, which is beneficial to the generation of efficient RTP. , The organic molecules containing heteroatoms such as O, N, and S or functional groups with lone electron pairs (aldehyde groups, carbonyl groups, CN, etc.)…”
Section: Introductionmentioning
confidence: 99%